2018
DOI: 10.1259/bjr.20170728
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of histological grade of hepatocellular carcinoma using quantitative diffusion-weighted MRI: a retrospective multivendor study

Abstract: All DW parameters could discriminate HCC grade. Non-ADC parameters might be more useful than the ADC for predicting poorly-differentiated HCCs. Advances in knowledge: The utility of quantitative DW parameters for predicting HCC grade was demonstrated by using multivendor MR units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…Ogihara et al confirmed the utility of diffusion-weighted imaging as an AF for HCC across a number of different vendors and b-values. 26 Another study by Shankar et al, noted a trend of decreasing ADC values in patients with HCC, correlated with increasing grade of the tumor. 27 This prospective study included patients with single observations identified on screening ultrasounds, which were subsequently characterized with contrastenhanced MRI (CE-MRI).…”
Section: Changes To Af In Li-rads V2017mentioning
confidence: 95%
See 4 more Smart Citations
“…Ogihara et al confirmed the utility of diffusion-weighted imaging as an AF for HCC across a number of different vendors and b-values. 26 Another study by Shankar et al, noted a trend of decreasing ADC values in patients with HCC, correlated with increasing grade of the tumor. 27 This prospective study included patients with single observations identified on screening ultrasounds, which were subsequently characterized with contrastenhanced MRI (CE-MRI).…”
Section: Changes To Af In Li-rads V2017mentioning
confidence: 95%
“…Biliary excretion occurs via the multidrug resistance-associated proteins MRP2 at the canalicular membrane. 26 In early as well as progressed HCC, OATP1B1/B3 expression is often either absent or reduced compared to background liver parenchyma, whereas MRP2 expression is often increased. 30 As a result, HCCs tend to be hypointense compared to the liver in the delayed/hepatobiliary phase.…”
Section: Contrast Agents Available For Use In Mri For Diagnosis Of Hccmentioning
confidence: 99%
See 3 more Smart Citations